#Missing to #Found: Exploring police Twitter use for missing persons investigations. (15th January 2021) - Ferguson, Lorna; Soave, Vincenzo
ABSTRACT: Thousands of people go missing each year in Canada, with recent figures noting over 70, 000 reports generated in 2019. While missing person cases can place strains on police resources, the use of Internet technology can attenuate some of the demands by aiding with the investigations. As a result, this exploratory study examines one social media tool, Twitter, for missing person investigations by police in Canada. Through logistic regression, we analyze 373 missing person tweets posted over two years (2017–2019) from 15 Canadian police services on Twitter to estimate which features are likely to increase public engagement (retweets, likes, and comments) with these tweets. Results reveal that there are several features significantly associated with higher engagement, such as images and hashtags, ergo increasing community outreach and participation, as well as the likelihood of efficiently and successfully solving these cases. Therefore, we suggest that having standardized components to missing person tweets will enhance the usefulness of this tool.